Land Degradation and Desertification a Global Crisis - Kaswamila, Abiud (IntechOpen, 2016)
Land degradation which is caused by multiple forces-extreme weather conditions and anthropogenic activities that pollute or degrade the quality of soils and land utility-negatively affects food production, livelihoods, and the provision of other ecosystem goods and services. Land degradation can also lead to climate change and affect human health. The problem is more pronounced in least developing countries due to overdependence of natural resources for survival. Sustainable ways to reduce land degradation and desertification demand research and advocacy of sustainable land management practices. This book is organized into two sections. The first section covers three major aspects, viz., an understanding of patterns of land degradation and desertification for developing mitigation strategies, land-atmosphere interaction from response of land cover to climate change effects of Karst rocky desertification, and the effect of unprecedented human activity into land degradation and desertification processes using natural and human-induced landscape research. The last section dwells on the relationship between soil degradation and crop production and an examination on how land degradation impacts the quality of soil in communal rangelands. Environmentalists, land-use planners, ecologists, pedologists, researchers, and graduate students will find this book to be an essential resource.